Alien plants in Western region, Saudi Arabia - AL-HARTHI, SAUD THAMER SAEED; AL-QAHTANI, ABDULLAH MANAHI; AL-MUNQEDHI, BANDAR MOHSEN (Journal of agricultural, environmental and veterinary sciences, 2019)
Urbanization in Saudi Arabia has led to the introduction of many exotic plant species as well as weeds, especially in the last few years that have never been seen before. The present study aims to identify the alien invasive species in the western region of Saudi Arabia, assessing the impacts of the invasive species on native plants as well as endemic plants and also the adverse effects of plants on the natural vegetation cover. Several field trips were made for plant collections and different categories of exotic plants were identified which include annual herbs and grasses, perennial herbs, sub shrubs, shrubs and trees. In the present study, 16 exotic plants were identified of which 14 belong to old world species and 2 belong to new world species (the plants from South America is the most representative of these species). These exotic species have caused a change in the composition of natural plant communities and have affected the diversity of native plants in natural habitats and protected areas. Examples of these plant species include: Argemone ochroleuca, Nicotiana glauca, Opuntia dillenii, Prosopis juliflora etc. Among these species P. juliflora, was found at low elevations such as valleys and farms while N. glauca and O. dillenii were observed at high elevations such as mountains.